Phase angle as an indicator of body composition and physical performance in handball players - Valmir Oliveira Silvino; Kelly Raffaela Barbosa Barros; Felipe Machado Brito; Francisco Matheus Dias Magalhães; Antônio Augusto Ferreira Carioca; Adriano César Carneiro Loureiro; Acácio Salvador Veras-Silva; Marcos Daniel Motta Drummond; Marcos Antonio Pereira dos Santos (BMC, 2024)
Abstract Background Phase angle (PhA), obtained from the bioimpedance analysis, is widely used in clinical situations and in sports. This study evaluated the association between PhA with body composition and physical performance of handball athletes. Methods 43 national-level players (22.19 ± 3.86 years) of both sexes were evaluated regarding anthropometry, body composition, squat (SJ) and countermovement (CMJ) jumps, handgrip strength, and cardiorespiratory fitness. Results We verified a correlation between PhA of the whole body and fat-free mass (r = 0.511), body mass index (r = 0.307), and body fat % (r = -0.303). There was a positive correlation between PhA of the whole body and SJ (r = 0.376), CMJ (r = 0.419), and handgrip for the dominant hand (r = 0.448). Moreover, PhA of the upper limbs was more strongly correlated with handgrip for the dominant (r = 0.630) and non-dominant hand (r = 0.575) compared to PhA of the whole body considering both sexes. Similarly, segmental PhA had a stronger significant correlation with SJ (r = 0.402) and handgrip for the dominant hand (r = 0.482) in males, as well as CMJ (r = 0.602) in females, compared to PhA of the whole body. Conclusion PhA of the whole body was positively related to fat-free mass, body mass index, body fat %, and lower- and upper-limbs strength in handball athletes. Segmental PhA might be used as a tool for estimating lower and upper limbs performance considering the sex, in preference to the PhA of the whole body.